BIRDS AND BEASTS WERE MANY: THE ECOLOGY AND CLIMATE OF THE GUANZHONG BASIN IN THE PRE-IMPERIAL PERIOD. (September 2020) - Lander, Brian
Abstract: This paper reviews current knowledge on the geography, climate, flora, and fauna of Shaanxi's Guanzhong 關中 Basin, a region that has been particularly well studied because it was a capital region of the Zhou, Qin, Han, and Tang dynasties. Humans have so thoroughly transformed the region that it is hard to imagine that it was ever full of wild plants and animals. And since much of the English-language scholarship on the Zhou period focuses on the texts and ideas of urban elites, it is easy to forget that most people were rural farmers living in environments full of wild plants and animals, and that many places had no humans at all. Scholars in various fields have produced abundant new information on the environments of ancient China, making it possible to reconstruct climate and ecology far more accurately than was possible before. This research shows that, contra older claims that ancient North China had a subtropical climate, the climate of the Neolithic and Bronze Age periods was only slightly warmer and wetter than the present. The most important factor in the transformation of the region's ecosystems has been humans, not climate. We will focus on the pre-imperial period because various lines of evidence suggest that the first millennium b.c.e . was a period of population growth in which agricultural societies wiped out many of the natural ecosystems of lowland North China. Only by reconstructing what North China looked like thousands of years ago will we be able to understand how humans came to be the dominant force in the region's ecology.